OCCUPATIONAL SAFETY MANAGEMENT IN CIVIL AVIATION AS AN ELEMENT OF THE QUALITY MANAGEMENT SYSTEM - SKIBITSKA, Liana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores occupational safety management in civil aviation as an integral component of the quality management system. The author substantiates the close interconnection between the effective organization of occupational safety and the overall quality of an aviation enterprise’s operations. The article provides a comprehensive analytical assessment of the factors involved in integrating occupational safety into the quality management system, and examines current challenges, including those related to martial law, cyber threats, the implementation of unmanned technologies, and the need for decarbonization in the aviation industry. The central idea is that aviation must adapt to complex conditions that threaten both operational safety and sustainable development. Attention is also given to international experience and examples of SMS/QMS implementation in leading countries. The author proposes a conceptual model for occupational safety management based on the principles of Total Quality Management, the Viable System Model, and strategic management. As a result of the study, the necessity of an integrated approach to forming a quality management system (QMS) in aviation enterprises is substantiated—one that ensures risk reduction, improved service quality, and organizational resilience to external challenges. Future research prospects include the development of digital tools for evaluating safety indicators, harmonizing standard requirements, and strengthening the role of human capital in occupational safety management.